Development and application of a dynamic conflict resolution method for integrated water resources management / Mehdi Zomorodian - Mehdi , Zomorodian (2018)
Water, a vital resource for human life and civilization, is heterogeneously distributed spatially and temporally. This inevitably leads to conflicts as the water demand is dramatically increasing due to population and socio-economic growth and climate change can exacerbate the situation. Early conflict resolution efforts were based on traditional linear thinking paradigm and “win-lose” understanding of the problems. These efforts suffer from lack of organizational and mental structure for sustainable development, therefore they fail to address primary drivers of water resources problems. Modeling of conflict requires a correct understanding of stakeholders and decision-makers, their preferences, strategies, and actions. As game theory provides a mathematical framework for better understanding of these key elements, it has been used to develop some successful cooperative and non-cooperative game models for conflict resolution. However, there are still weaknesses in determining optimal allocation, especially for rapid-changing multi-reservoir systems. Developing an integrated management tool by considering the internal and external dynamics of sub-systems can certainly improve the available approaches. This study, as a step towards consideration of the above issues in multi-reservoir system operation and management, puts a simulation-optimization modeling approach forward based on the game theory and system dynamics concepts. In this study, sub-systems in a water resource system were first identified, and the associated key factors, dynamics, and interactions of these sub-systems were modeled by employing system dynamics. Then an allocation optimizer was developed to find the best water allocation to each sub-system based on Nash Bargaining Solution. Based on this concept, three continuous models have been developed. In the first model, all components play pure-strategy games while in the second and third models, the reservoir components take the uncertainty of inflow into account by utilizing a combination of a mixed-strategy game and the Markov chain method. Next, a case study focusing on Langat River Basin and its associated area was carried out, to evaluate the efficiency of the proposed method. While all the models were used to evaluate the capabilities of the proposed method between 1992 and 2013, the third model representing the catchment in more details was used to analyze five managerial scenarios, and the possible consequences between 2014 and 2030. Finally, performance indices were calculated to evaluate the efficiency of each model. According to the results, the presented method is capable of tackling conflict issues in water allocation in situations of water scarcity as the performance indices were considerably high for all three models. However, utilizing the combination of Markov chain method and mixed-strategy game to deal with the uncertainty of inflow improved the performance. From the scenario analysis, the “Business as usual” scenario evaluated the worst condition. Meanwhile, reducing the non-revenue water (NRW) and water use per capita (WUPC) reduced the unmet demand dramatically. Also, providing additional potable water to the system was not evaluated as an appropriate decision without managing the WUPC and NRW. According to the results, a combination of these three scenarios was assessed as relatively the best managerial scenario for Langat River Basin.